Experimental Drought Suppresses Amphibian Pathogen Yet Intensifies Transmission and Disrupts Protective Skin Microbiome - Shannon Buttimer; Daniel Medina; Renato A. Martins; Ana Gabrielle Morais da Silva; Wesley J. Neely; Célio F. B. Haddad; Graziella V. DiRenzo; Alessandro Catenazzi; Rayna C. Bell; C. Guilherme Becker (Global Change Biology, 2025)
Shifting precipitation regimes driven by global climate change can alter vertebrate behavior and host‐symbiont relationships, potentially compromising host resistance to pathogen invasion. In Brazil's Atlantic Forest, a biodiversity hotspot, prior research identified drought as a key factor disrupting the skin microbiome, contributing to a die‐off of pumpkin toadlets due to the invasive waterborne fungal pathogen Batrachochytrium dendrobatidis (Bd). However, observational studies cannot disentangle the direct effect of moisture on Bd growth from increased amphibian activity during wet breeding seasons. Using field enclosures, we experimentally tested the influence of drought conditions on host microhabitat use, Bd disease dynamics, and the composition and predicted Bd‐inhibitory function of cutaneous bacterial communities. Each enclosure housed ecologically realistic densities of Brachycephalus pitanga , a micro‐endemic pumpkin toadlet. We simulated a short‐term drought in half of the enclosures using translucent tarp coverings. To track individual toadlets, we identified their unique markings and collected skin swabs biweekly over 3 months. We then implemented molecular techniques to quantify Bd loads and characterize skin bacterial diversity and composition over time. Our findings indicate that while drought may reduce overall Bd loads on hosts, this effect is partially offset by an increase in the use of water‐filled areas of the enclosures and by a disruption of the protective host skin microbiome. This study provides valuable insights into the cascading impacts of climate change on animal behavior, host‐symbiont interactions, and disease dynamics.